Focal adhesion kinase promotes aerobic glycolysis in hepatic stellate cells via the cyclin D1/c-Myc/MCT-1 pathway to induce liver fibrosis - Tao Huang; Ming-Yu Zhou; Gao-Liang Zou; Rui-Han Hu; Lu Han; Qing-Xiu Zhang; Xue-Ke Zhao (Scientific Reports)
Abstract Hepatic stellate cells (HSCs) transdifferentiate into myofibroblasts during liver fibrosis and exhibit increased glycolysis. Phosphorylated focal adhesion kinase (FAK) (pY397-FAK) promotes monocarboxylate transporter 1 (MCT-1) expression in HSCs to increase aerobic glycolysis and cause liver fibrosis. A combined multiomics analysis of C57BL/6 mice with tetrachloromethane (CCl4)-induced liver fibrosis was performed to identify the downstream FAK signaling pathway. The effect of the FAK inhibitor PF562271 on CCl4-induced liver fibrosis was explored by immunofluorescence of liver tissues. The migration, proliferation and aerobic glycolysis of LX-2 cells after stimulation and activation by transforming growth factor beta-1 (TGF-β1) or suppression by PF562271 was assessed in vitro. Multiomics analysis of a successfully generated CCl4-induced liver fibrosis mouse model was performed. FAK and cyclin D1 were significantly enriched in mice with CCl4-induced liver fibrosis. In vivo, the MCT-1 and alpha smooth muscle actin (α-SMA) levels were increased in mice with CCl4-induced liver fibrosis, and MCT-1 and α-SMA expression decreased after PF562271 treatment. In vitro, PF562271 alleviated TGF-β1-induced LX-2 activation. LX-2 cells showed diminished migration, proliferation, and aerobic glycolysis after PF562271 intervention. FAK promotes aerobic glycolysis in LX-2 cells through the cyclin D1/c-Myc/MCT-1 pathway, thereby increasing liver fibrosis.